MULTIFUNCTIONALITY OF DISCOURSE MARKER "PORTANTO" IN BRAGA’S SPEECH - MARQUES, Maria Aldina; AGUIAR, Micaela (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Multifunctionality of discourse marker portanto in Braga’s Speech. This paper explores the multifunctionality and usage patterns of the discourse marker portanto in Braga’s speech. Our main goal is to propose a revised description of portanto, while acknowledging the validity of previous research on the topic. The investigation focused on the co-occurrence of functions associated with portanto, emphasizing its pivotal role in speech construction. The frequency distribution of portanto usage was found to be consistent with earlier studies, affirming its most prevalent application as a filler (marker). Our study also highlighted that an excessive use of discourse markers can create the illusion of coherence, rather than genuinely ensuring it, especially in contexts characterized by frequent pauses, verbal hesitations, and syntactic interruptions. Furthermore, this research examined the influence of discourse genre on portanto’s usage patterns. Notably, the two predominant uses observed in Braga’s speech were linked to specific aspects of sociolinguistic interviews, particularly the recollection of life stories and features of spontaneous speech. The findings enrich our understanding of this discourse marker's multifaceted role in facilitating coherent communication and its significance in various speech contexts. REZUMAT. Multifuncționalitatea marcatorului discursiv portanto în graiul din Braga. Acest articol explorează multifuncționalitatea și modelele de utilizare ale marcatorului discursiv portanto în graiul din Braga. Scopul nostru principal este să propunem o descriere revizuită a marcatorului portanto, recunoscând în același timp validitatea cercetărilor anterioare. Cercetarea noastră s-a concentrat asupra co-ocurenței funcțiilor marcatorului portanto, care subliniază rolul esențial al acestuia în coeziunea discursului. Distribuția frecvenței utilizării lui portanto s-a dovedit a fi în concordanță cu studiile anterioare, confirmând că cea mai frecventă utilizare este de marcator. Studiul nostru a subliniat, de asemenea, că utilizarea excesivă a marcatorilor discursivi poate crea iluzia coerenței, fără însă a o asigura cu adevărat, mai ales în contexte caracterizate de pauze frecvente, ezitări verbale și discontinuități sintactice. În plus, cercetarea noastră a examinat și influența genului discursiv asupra modelelor de utilizare ale marcatorului portanto. Cele două utilizări predominante observate în graiul din Braga au fost influențate de aspecte specifice ale interviurilor sociolingvistice, în special nararea poveștilor de viață și trăsăturile discursului spontan. Concluziile noastre contribuie la înțelegerea rolului multifațetat al acestui marcator discursiv în facilitarea comunicării coerente și clarifică sensurile sale în mai multe contexte. Cuvinte-cheie: graiul din Braga, registrul colocvial, marcatori discursivi, portugheză europeană, multifuncționalitate. Article history: Received 28 July 2023; Revised 2 November 2023; Accepted 12 November 2023; Available online 20 December 2023; Available print 31 December 2023.